Beyond the Hype: How Does AI Truly Compare to Humans in Disease Diagnosis? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Beyond the Hype: How Does AI Truly Compare to Humans in Disease Diagnosis? The integration of Artificial Intelligence (AI) into healthcare is rapidly tr...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Precision Medicine